2012
DOI: 10.1007/s00227-012-2121-4
|View full text |Cite
|
Sign up to set email alerts
|

Increased carbon dioxide availability alters phytoplankton stoichiometry and affects carbon cycling and growth of a marine planktonic herbivore

Abstract: Rising levels of CO 2 in the atmosphere have led to increased CO 2 concentrations in the oceans. This enhanced carbon availability to the marine primary producers has the potential to change their nutrient stoichiometry, and higher carbon-to-nutrient ratios are expected. As a result, the quality of the primary producers as food for herbivores may change. Here, we present experimental work showing the effect of feeding Rhodomonas salina grown under different pCO 2 (200, 400 and 800 latm) on the copepod Acartia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 59 publications
7
63
1
2
Order By: Relevance
“…At the same rate as media was pumped in, culture overflowed into a sterile overflow bottle, which was sampled for subsequent biochemical and other analyses. The out-flowing culture was collected in sterile 1 L glass overflow bottles, providing culture material for subsequent analyses (Figure 1), as has been performed elsewhere [17]. Use of an overflow vessel to collect surplus culture allowed us to measure a suite of biochemical parameters for which large volumes of culture were required (up to 700 mL).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same rate as media was pumped in, culture overflowed into a sterile overflow bottle, which was sampled for subsequent biochemical and other analyses. The out-flowing culture was collected in sterile 1 L glass overflow bottles, providing culture material for subsequent analyses (Figure 1), as has been performed elsewhere [17]. Use of an overflow vessel to collect surplus culture allowed us to measure a suite of biochemical parameters for which large volumes of culture were required (up to 700 mL).…”
Section: Methodsmentioning
confidence: 99%
“…Elevated CO 2 concentration has been shown to influence the ratio of carbon to nutrient uptake rates in phytoplankton [13][14][15][16] and consequently an increase in C:N:P ratio [17][18][19]. A reduction in the percentage of polyunsaturated fatty acids (PUFA) in the diatom Thalassiosira pseudonana has also been reported [20].…”
Section: Introductionmentioning
confidence: 98%
“…For instance, Teoh et al (2004) reported a significant decrease in polyunsaturated fatty acids (PUFA) at temperatures above 4 • C in an Antarctic strain of Navicula sp. In addition, cellular fatty acid (FA) composition and nutrient stoichiometry can be directly related to the food quality transferred to higher trophic levels and may be negatively affected by ocean acidification (Riebesell et al, 2000;Rossoll et al, 2012;Schoo et al, 2013). However little is known about the combined effects of ocean acidification and warming on microalgal lipid FA composition.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Urabe et al (2003) found lower growth rates of the freshwater species Daphnia pulicaria at high pCO 2 due to altered algal C:P ratios. Schoo et al (2013) found that the copepod Acartia tonsa showed decreased development rate when fed the algae Rhodomonas salina grown under increased pCO 2 levels. In a culture containing the diatom Thalassiosira pseudonana and the copepod Acartia tonsa, Rossoll et al (2012) found that exposure to pCO 2 levels of 750 µatm led to a decrease in polyunsaturated fatty acids in the diatoms and a corresponding decrease in copepod egg production (Rossoll et al 2012).…”
Section: Copepod Body Conditionmentioning
confidence: 98%
“…Under high pCO 2 conditions, increasing carbon availability has the potential to change the stoichiometry of nutrients to primary producers. Carbon to nutrient ratios, which are already comparatively high in diatoms, will increase under such scenarios, making them of inferior quality to herbivorous consumers (Sterner and Elser 2002, Boersma et al 2008, Malzahn et al 2007, Schoo et al 2013, Nobili et al 2013. The lower enzymatic specificity for CO 2 in dinoflagellates makes them less responsive to CO 2 enrichment and their carbon to nutrient ratios are less affected than diatoms (Tortell 2000), and they retain their quality as food items.…”
Section: Dinoflagellate Response To Acute Pco 2 Elevationmentioning
confidence: 99%